Development of cafÃ© web-based system using priority scheduling approach - Ghazali, Fatimah; Ismail, Rohana; Hariz Hasni, Mohamad (International Journal of Engineering and Technology, 2018)
Manual food ordering system requires on many employees to handle ordering process. It can be dull and disorganized, and can end up with data irregularity for generating sales report. Moreover, the total time taken for food preparations is longer.Â Therefore, the cafÃ© web based system is developed using priority scheduling algorithm to reduce the duration in ordering process, handling and preparing bulk and concurrent order, and at the same time minimizing the cost of handling employees. The priority scheduling algorithm is based on Control Processing Unit scheduling algorithm where it has a priority to execute tasks in waiting queue. The system is implemented at UniSZAâ€™s cafÃ© where it will be used by cafÃ© owner and UniSZA students. This system is developed based on three-tier architecture. The JSP, JavaScript, Java and MySQL have been employed to improve manual ordering management. Initially, the preliminary testing shows that the priority scheduling algorithm has a potential to exchange the traditional ordering system.Â